Evaluación de la capacidad de alojamiento de paneles fotovoltaicos en la red de distribución de líneas primarias usando OpenDSS en el alimentador Chimbo de la subestación Guaranda de la Unidad de Negocio Bolívar CNEL EP. - Pazmiño Gavilanes, Edwin David (2023)
The reduction of the greenhouse effect such as CO2, has made many countries take alternatives to reduce the environmental impact guided by the objectives of the 2030 diary. Due to this, the electrical power system and mostly distribution networks ’on are changing the mode of operation and planning, where these must consider the massive income of renewable energy such as photovoltaic panels, wind generators and electric vehicles. The entry of this type of technology can cause voltages outside the permitted limit, fluctuations, chargeability, reverse flows, sympathetic firing, increased fault currents, etc. Therefore, an assessment of the percentage of income from renewable sources must be carried out. In this way, in our investigation an evaluation of the accommodation capacity of photovoltaic panels in the distribution network of primary and secondary lines is carried out using OpenDSS in the Chimbo feeder of the Guaranda substation of the Bol´ıvar CNEL EP business unit . For this, two methodologies are presented, the first one evaluates the maximum input capacity of photovoltaic panels in percentage and the second methodology is to carry out a reactive power-voltage control through an optimization model. that allows up to 100 % of photovoltaic panels to enter the network without exceeding the limits of energy quality allowed in national regulations. The results with the first methodology show that 48 % (3305 photovoltaic panels ) is the máximum income limit for the Guaranda Chimbo feeder and applying the second methodology, 100 % (6887 photovoltaic panels ) can be entered.